Pendidikan Kewarganegaraan Berwawasan Global Untuk Penanaman Kecakapan Belajar Dan Berinovasi Warga Negara Abad Ke-21 - Sutrisno Sutrisno (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to analyze the role of citizenship education with a global perspective to instill learning skills and innovate in 21st-century citizens. This research is qualitative research using a special study approach. Data collection techniques with observation interviews and documentation. . The results of the study show that citizenship education with a global perspective can foster the Learning and Innovation skills of 21st-century citizens through a learning process using the global citizen project model. Global citizen project. is a green design learning model for citizenship education with a global outlook that develops the skills of young citizens in critical thinking and problem-solving, communication and collaboration as well as creativity and innovation in solving complex global problems.